Church Proprietorship in Nigeria: A Factor for a Shift from the Paradigm, 1980-2015 (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2023)
Christianity as a religion came with the foundational teachings, practices and beliefs of the early Christian Church. The constituents of the paradigm were established by Jesus Christ and the apostles. The corpus teachings revolved on monotheism (through trinity), salvation, spiritual growth, fellowship, community and love. The religion was introduced to Nigeria, first to Benin City in the present day, Edo State in 1486, and second, to other parts of Nigeria in the 19th century with these core teachings, practices and beliefs. This study is a strict interrogation of how church of Christ subsisted under proprietorship in Nigeria. It observed the distortions that were inherent in proliferation of churches under private ownership and control.  The division of the Christendom, and the subsequent proliferation of Churches in the world that transcended to Nigeria depicted continuous sprouting of churches at any slightest excuse. It is therefore, discovered that absence of visible and instant punishment for emotional, selfish and inaccurate interpretation of the scriptures to suit and satisfy one’s desire and interest results in increasing and uncontrollable sprouting of Churches. Investigation further revealed that privatization and commercialization of the gospel, prioritization of church-growth over spiritual growth, and a shift from servant-leadership to authoritarian leadership, and self-actualization resulted in compromise on biblical teachings for popularity and profit-making. Of course, the effort for financial and material gains remains principal in proprietorship. Primary and secondary sources were relied on while its data were analyzed qualitatively, using content analysis and thematic approaches.Christianity as a religion came with the foundational teachings, practices and beliefs of the early Christian Church. The constituents of the paradigm were established by Jesus Christ and the apostles. The corpus teachings revolved on monotheism (through trinity), salvation, spiritual growth, fellowship, community and love. The religion was introduced to Nigeria, first to Benin City in the present day, Edo State in 1486, and second, to other parts of Nigeria in the 19th century with these core teachings, practices and beliefs. This study is a strict interrogation of how church of Christ subsisted under proprietorship in Nigeria. It observed the distortions that were inherent in proliferation of churches under private ownership and control.  The division of the Christendom, and the subsequent proliferation of Churches in the world that transcended to Nigeria depicted continuous sprouting of churches at any slightest excuse. It is therefore, discovered that absence of visible and instant punishment for emotional, selfish and inaccurate interpretation of the scriptures to suit and satisfy one’s desire and interest results in increasing and uncontrollable sprouting of Churches. Investigation further revealed that privatization and commercialization of the gospel, prioritization of church-growth over spiritual growth, and a shift from servant-leadership to authoritarian leadership, and self-actualization resulted in compromise on biblical teachings for popularity and profit-making. Of course, the effort for financial and material gains remains principal in proprietorship. Primary and secondary sources were relied on while its data were analyzed qualitatively, using content analysis and thematic approaches.